Applying the payment card approach to estimate the WTP for green food in China - Xu Tian; Xiaohua Yu; Rainer Holst (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
This paper uses a payment card approach to reveal consumers' willingness to pay for green food in China. We first present a brief introduction of the payment card approach and introduce several methods to estimate the WTP with payment cards, which we subsequently use to estimate WTP values regarding green vegetables, green meat and green eggs in China. Our results indicate that consumers in big cities are willing to pay a higher premium for green food and that WTP values are relatively higher for more expensive food than for cheaper food. In addition, the ratios of premium to price range mainly between 25% and 50% and WTP values obtained from interval midpoint approach are relatively higher than those calculated by other approaches.
Keywords: 330; WTP; Payment card; Green food